Pengaruh Konsentrasi Natrium Hidroksida dan Waktu Pemasakan Terhadap Penurunan Kadar Lignin Menggunakan Kulit Edamame (Glycin Max (L) Merill) dengan Proses Soda - Tri Suharni; Ahmad M Fuadi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The increase in demand for pulp and kertas raises awareness of the problem of kayu hutan as the primary raw material for pulp and kertas production. As a result, an alternative to kayu is required. One non-kayu tanaman that has the potential to be used as an alternative raw material in pulp production is edamame kulit (Glycin max (L) merrill), which is slowly brewed or baked such that it can cause environmental problems. Kulit edamame has a relatively high selulosa content of 2.3% to 13.1%. This study aims to understand the effects of pemasakan and the concentration of natrium hydroxide on the lignin pulp from kulit edamame using the soda process. The best method for this study is to use NaOH concentrations of 0.7%, 0.9%, and 1.78%, 1.82, and 1.86 percent at pemasakan times (100, 115, 125, 135, 145 menit) has lignin tertinggi kadar of 2,0376% and lignin terendah kadar of 0,9000%. The purpose of this study is to determine the pulp quality that is obtained from the soda process using NaOH concentration and the best combination of NaOH concentration and pemasakan time in the production of pulp from Kulit Edamame. The results of the study show that as the concentration of NaOH increases, the amount of lignin will decrease. This is because increasing the concentration of pemasakan's lignin can increase the amount of delignification and the amount of lignin that degrades will result in better pulp. And the longer the pemasakan time, the longer the lignin kadar will flow, resulting in a pulp that is more putih and has better quality.